Composition of the Gas-Air Mixture in the Containment and Suppression of Forest Fires with Promising Extinguishing Agents; Forests; Vol. 14, iss. 4 - Kropotova S. S. Svetlana Sergeevna; Dorokhov V. V. Vadim Valerjevich; Sviridenko A. S. Aleksandr Sergeevich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen